Przyjazna oficyna. Adam Czerniawski i Bednarczykowie - Kisiel, Marian (Tematy i Konteksty, 2024)
This article discusses the ties between Adam Czerniawski (1934–2024) and Krystyna and Czesław Bednarczyk’s Poets and Painters Press. Their press published Czerniawski’s early collections of poetry, essays, and fiction. It is argued that without the Poets and Painters Press Czerniawski would not have gained recognition and publicity during the peak of his artistic activity in 1956–1977